(untitled) (Asian Journal of Agriculture, 2021)
Abstract. Prajapati HR. 2021. Use of duality theory in organic farming: evidence from India. Asian J Agric 5: 45-52. The duality analysis provides an alternative way for solving the problem of cost minimization. In this method, a specified suitable cost function has been used as an objective function with certain constraints, rather than using production functions. In duality theory, both cost and profit functions are used as an objective function under a well-defined production technology along with related behavioral assumptions. This paper has applied translog cost function as an objective function under certain input constraints for the estimation of five input parameters viz. Land, Labor, Capital, Machinery, and Irrigation based on field survey data of 284 organic and non-organic wheat producers in four rain-fed districts of Gujarat. Based on these parameters, all inputs price elasticity and elasticity of input substitution have been calculated using Iterated Smilingly Unrelated Regression Equations (ISURE) method of estimation. The results of the estimation, for both organic and non-organic farms, have found both positive and negative signs as was expected theoretically but the value is not significant.